(untitled) (Research, Society and Development, 2025)
The dimensioning of the Community Health Agent’s (CHA) territory, based on a quantitative ceiling, generates overload and inequities by ignoring the complexity of different social and health realities. This article proposes and evaluates the ÍCARO (Operational Risk-Load Index), an innovative theoretical model aimed at replacing headcounts with a metric of actual workload. Through a theoretical essay with computational simulation, two calibrations of the model (ÍCARO-1 and ÍCARO-2) were tested, both integrated with the Coelho & Savassi family risk classification and set to a 750-point target. A total of 10,000 micro-areas with demographic profiles from Porto Velho-RO (IBGE) were simulated, revealing that a CHA’s coverage capacity can vary drastically from 455 to 964 people to maintain an equitable workload. It is concluded that the ÍCARO model is not just a fairer alternative, but a strategic management tool that allows managers to make evidence-based decisions, qualify the work in Primary Health Care, and effectively operationalize the principle of equity.